The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fnmol.2022.1038539
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA sequencing reveals distinct transcriptional features of the purinergic signaling in mouse trigeminal ganglion

Abstract: Trigeminal ganglion (TG) is the first station of sensory pathways in the orofacial region. The TG neurons communicate with satellite glial cells (SGCs), macrophages and other cells forming a functional unit that is responsible for processing of orofacial sensory information. Purinergic signaling, one of the most widespread autocrine and paracrine pathways, plays a crucial role in intercellular communication. The multidirectional action of purinergic signaling in different cell types contributes to the neuromod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Among them, 61 candidate proteins were then filtered for being a bona fide secreted factor, i.e., possessing a signal peptide, 11 of which have the specific receptor(s) documented (Supplementary information, Table S1 ). We further analyzed the expression of these receptors in the published single-cell RNA-seq (scRNA-seq) dataset of mouse trigeminal ganglionic neurons (GSE213105), 25 whose axonal projections control Me5-L/-R and 5N-L/-R, the signature regions activated by multiple cancer types. Through this multi-omic screening, three candidate proteins (LIF, pigment epithelium-derived factor, and thrombospondin-1) were obtained for in-depth functional examination (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, 61 candidate proteins were then filtered for being a bona fide secreted factor, i.e., possessing a signal peptide, 11 of which have the specific receptor(s) documented (Supplementary information, Table S1 ). We further analyzed the expression of these receptors in the published single-cell RNA-seq (scRNA-seq) dataset of mouse trigeminal ganglionic neurons (GSE213105), 25 whose axonal projections control Me5-L/-R and 5N-L/-R, the signature regions activated by multiple cancer types. Through this multi-omic screening, three candidate proteins (LIF, pigment epithelium-derived factor, and thrombospondin-1) were obtained for in-depth functional examination (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We note that the detailed mechanisms by which LIF and Gal3 induce brain responses warrant more in-depth investigations. Notably, in the multi-omic screening of cancer cell-derived signaling molecules, we analyzed the expression of the putative receptor(s) for each candidate in the published scRNA-seq dataset of mouse trigeminal ganglionic neurons, 25 whose axonal projections control Me5-L/-R and 5N-L/-R, the signature regions activated by multiple peripheral tumors. This scRNA-seq analysis revealed that the LIF receptor ( Lifr ) is highly expressed in those neuronal populations (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The ABCB10 transporter is also downregulated by NMN exposure. ABCB10 has been shown to be highly expressed in neurons, and it has been suggested to play a role in the regulation of mitochondrial function in these cells [ 63 ]. It has been implicated in the response to oxidative stress, which is a common feature of many neurological disorders [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Current studies disagree about whether Panx1 upregulation primarily occurs in sensory neurons or their satellite cells, with one study finding expression mainly in neurons following SNI surgery in rats [ 126 ], and another finding that deletion of Panx1 in GFAP-expressing cells greatly reduced the pain response in a murine model of orofacial inflammatory pain [ 123 ]. Under homeostatic conditions, single-cell RNAseq identified higher and more widespread Panx1 expression in TG neurons than in supporting glia [ 127 ]. Astrocytes also express Panx1, which plays a critical role in ATP signaling, can bind to P2X7, and can potentiate the release of IL-1β [ 128 , 129 , 130 ].…”
Section: Sgcs and Astrocytes In Neuropathic Painmentioning
confidence: 99%